Relationships of working conditions, health problems and vehicle accidents in bus rapid transit (BRT) drivers (2018)
Background The aim of this study was to estimate accident risk rates and mental health of bus rapid transit (BRT) drivers based on psychosocial risk factors at work leading to increased stress and health problems. Methods A cross‐sectional research design utilized a self‐report questionnaire completed by 524 BRT drivers. Results Some working conditions of BRT drivers (lack of social support from supervisors and perceived potential for risk) may partially explain Bogota's BRT drivers’ involvement in road accidents. Drivers’ mental health problems were associated with higher job strain, less support from co‐workers, fewer rewards and greater signal conflict while driving. Conclusions To prevent bus accidents, supervisory support may need to be increased. To prevent mental health problems, other interventions may be needed such as reducing demands, increasing job control, reducing amount of incoming information, simplifying current signals, making signals less contradictory, and revising rewards.